ECTHR_CHAMBER 69116/01 vom 14. Juni 2005 , AFFAIRE MAYALI c. FRANCE - Ecthr Chamber (2005)
Violation de l'art. 6-1;Violation de l'art. 6-3-d;Préjudice moral - réparation pécuniaire; Violation: 6;6-1;6-3-d